Sustainable weed management using allelopathic approach - Nornasuha Y.; Ismail B.S. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Allelopathy is a natural phenomenon whereby, the donor plants release chemical compounds (known as allelochemicals) into the environment through decomposition, leaching (caused by rain water), volatilization and root exudates. Allelochemicals from the donor plants can stimulate and/or inhibit the germination and growth of the receiver plants. Allelopathic effects can be categorized based on the following: the effect of the weed on the crop, the effect of the weed on other weeds, the effect of the crop on the weed and the effect of trees on the weed or crop. Thus, allelopathic research can involve several methods such as bioassay, application of plant debris, application of infested soil, the sandwich method, the dish pack method and the plant box method. The allelopathic approach can be applied for controlling weeds through the use of allelochemicals (as natural herbicides) and the allelopathic plants as cover crops/mulch. However, the allelopathic effects of plants depend on biotic and abiotic factors and therefore, more research needs to be carried out to overcome these factors. The allelopathic approach would cause reduction in the dependency on chemical pesticides which are proven contaminants of the environment.